Beyond the Tax Code: Enhancing Taxpayer Compliance through Service, Counseling, and Public Relations - Salsabila, Nirwana; Qadri, Resi Ariyasa (WIM Solusi Prima, 2024)
The primary objective of this research is to elucidate the efficacy of service provision, counseling, and public relations implementation through the lens of management functions, namely planning, organizing, leading, and controlling. To address the central research question, a critical paradigm is employed, facilitating a rigorous critique of tax policies and their practical implications. Employing a qualitative research methodology, this study integrates a multi-method approach that amalgamates both primary and secondary data sources. The primary data are derived from the researcher's participant observations, conducted from 2021 to 2023 within the capacity of a taxpayer stationed at the Small Tax Office of Natar, subjected to thematic analysis. Secondary data, comprising statutory regulations and reports, were collated through the regulation documentation and subjected to analysis via a normative juridical approach. The findings indicate that the execution of service, counseling, and public relations activities remains suboptimal. Specifically, while the management functions of planning, leading, and controlling within service and counseling activities necessitate preservation, the organizing function demands significant enhancement. This study implies that extension activities is requisite for maintaining the planning and control functions, yet call for substantial improvements in organizing and leading functions.